Role conflict, work-family conflict and job satisfaction among single mother employees. - Ahmad, Aminah; Ngah, Noryati (2009)
Despite previous studies on job satisfaction and its antecedents, few studies have explored the interrelationships between role conflict, work-family conflict and job satisfaction. The purpose of this study is to determine the effect of role conflict on job satisfaction, with work-family conflict as a potential mediator. Data were gathered from 159 Malaysian single mother employees, aged 45 and below, using self-administered questionnaires. Results of regression analyses indicate that work-family conflict serves as one of the mechanisms through which role conflict influences job satisfaction. Role conflict experienced at the workplace can increase the interrole conflict between work and family domains which in turn can reduce the level of job satisfaction. The findings suggest that to improve the job satisfaction of employees the management should avoid seeing the problem of work in isolation from the total life space of employees.